Traditional Method vs AI Chatbot-Assisted in Arabic Learning - Siti Shalihah; Heru Fradana; Badr Nasser Aljabr (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
This study aims to compare the effectiveness of traditional Arabic language learning methods with AI-assisted learning using the Smojo.AI chatbot in improving students' reading skills. Using a mixed-methods approach, this research involved both quantitative and qualitative data collected from pre- and post-tests, interviews, and observations. The experimental group utilized the AI-powered Smojo.AI chatbot, while the control group followed traditional learning methods. The findings reveal that the experimental group demonstrated significant improvement in reading skills, with a higher post-test mean score compared to the control group, which showed a decline in performance. Statistical analysis confirmed the effectiveness of AI-assisted learning in enhancing students' Arabic language skills, especially in reading. This research contributes to the ongoing discussion about integrating technology into language education, offering valuable insights into the potential of AI tools in modernizing Arabic language teaching.